DIPG-49. International preclinical drug discovery and biomarker program informing an adoptive combinatorial trial for DMG. (3rd June 2022) - Nazarian, Javad; Dun, Matthew; Kilburn, Lindsay; Waszak, Sebastian; Vitanza, Nicholas; Franson, Andrea; Prados, Mike; Raabe, Eric; Firestein, Ron; Beck, Alexander; Saratsis, Amanda; Rotblat, Barak; et al.
Abstract: INTRODUCTION: DMG-ACT (DMG- multi-arm Adaptive and Combinatorial Trial) will implement an innovative clinical trial design of combinatorial arms for patients with DMG at all disease stages, that is adaptive to pre-clinical and correlate data generated in eight collaborating institutions. The goal of the team is to rapidly identify and validate i) promising drugs and drug combinations for clinical use, and ii) predictive biomarkers of promising drugs. METHODS: In vitro (n=30) and in vivo (n=8) models of DMG across fourteen institutions were used to assess single and combination treatment of over 80 drugs and drug combinations. Predictive biomarkers of response for top candidate drugs were identified using extensive molecular assays including proteomics, CRISPR, RNAseq, ELISA, FACS, and IHC. RESULTS: Inhibitory concentration (IC50) of all drugs were established and validated across all participating sites. In vivo validation of single and combination drug assays confirmed drug efficacy as increased survival for: ONC201 (p=0.01), ONC206 (p=0.01), ONC201+ONC206 (p=0.02), ONC201+panobinostat (p=0.01). Marizomib was highly toxic in murine PDX and zebrafish larvae assays. Murine pharmacokinetic analysis showed peak brain levels of ONC201, and ONC206 above pre-clinical IC50 concentrations. Molecular testing and analyses of existing drug screen across 578 cancer cells validated mitochondrial stress and additional proteins, as the main targets induces by ONC201/6. CONCLUSION: Thorough preclinical testing in a multi-site laboratory setting identified promising therapeutics for DMGs, resulting in launch of two clinical trials (PNOC022, ONOC023). Validation of identified biomarkers are ongoing using clinical specimen as well as in vivo PDX models.